Construction of Ecological Conservation and Assessment of Its Impact on Environment (Journal of Environmental Science Studies, 2022)
In recent years, environmental problems caused by global warming--- melting glaciers, rising sea levels, frequent wildfires and the death of large coral reefs, moved from the pages of the books to reality. To solve the problem, we develop several mathematical models, using both qualitative and quantitative methods, analyzing the importance of each influencing factor, finally build evaluation model of ecological environment and nature reserve. Firstly, in order to make a comparative analysis of the environmental conditions before and after the restoration of Saihanba, I collect the data of forest coverage rate, water conservation, PM2.5, oxygen release and carbon dioxide absorption of Saihanba in 60 years from 1962 to 2021, establishing Entropy Weight Method and Technique for Order Preference by Similarity to an Ideal Solution model (EWM-TOPSIS). Obtained that water conservation was the index with the largest weight, forest coverage rate is the index with the least weight, and the ecological environment in this area is the best in 2021 and the worst in 1962, indicating that saihanba restoration plays a significant role in improving the environment in this area. Secondly, I analyze the correlation between saihanba and Beijing's ecological environment, and qualitatively judge the degree of impact between the two. Then I take five ecological environment indexes of Saihanba as independent variables and four indexes of Beijing's anti-sandstorm ability as dependent variables of four Multiple Linear Regression models (MlR), which helps me make quantitative judgment, and finally get the conclusion that the improvement of the ecological environment of Saihanba will promote the anti-sandstorm ability of Beijing. After modelling, I also conduct sensitivity analysis to experiment the sensitivity of some parameters included in my models. In the end, I summarize strengths and weaknesses and a brief conclusion is also presented.